TRAINING EXPERIENCE: DIDACTIC STRATEGY FOR TEACHING FREQUENTIST PROBABILITY IN A NON-EQUIPROBABLE SAMPLE SPACE - Chavarría Brenes, Luis Diego (2025)
A training experience: didactic strategy for teaching frequentist probability in a non-equiprobable sample space